Identification of resistant germplasm containing novel resistance genes at or tightly linked to the Pi2/9 locus conferring broad-spectrum resistance against rice blast - Xiao, Gui; Borja, Frances Nikki; Mauleon, Ramil; Padilla, Jonas; Telebanco-Yanoria, Mary Jeanie; Yang, Jianxia; Lu, Guodong; Dionisio-Sese, Maribel; Zhou, Bo (Springer, 2017)
The rice Pi2/9 locus harbors multiple resistance (R) genes each controlling broad-spectrum resistance against diverse isolates of Magnaporthe oryzae, a fungal pathogen causing devastating blast disease to rice. Identification of more resistance germplasm containing novel R genes at or tightly linked to the Pi2/9 locus would promote breeding of resistance rice cultivars. Results In this study, we aim to identify resistant germplasm containing novel R genes at or tightly linked to the Pi2/9 locus using a molecular marker, designated as Pi2/9-RH (Pi2/9 resistant haplotype), developed from the 5′ portion of the Pi2 sequence which was conserved only in the rice lines containing functional Pi2/9 alleles. DNA analysis using Pi2/9-RH identified 24 positive lines in 55 shortlisted landraces which showed resistance to 4 rice blast isolates. Analysis of partial sequences of the full-length cDNAs of Pi2/9 homologues resulted in the clustering of these 24 lines into 5 haplotypes each containing different Pi2/9 homologues which were designated as Pi2/9-A5, −A15, −A42, −A53, and -A54. Interestingly, Pi2/9-A5 and Pi2/9-A54 are identical to Piz-t and Pi2, respectively. To validate the association of other three novel Pi2/9 homologues with the blast resistance, monogenic lines at BC3F3 generation were generated by marker assisted backcrossing (MABC). Resistance assessment of the derived monogenic lines in both the greenhouse and the field hotspot indicated that they all controlled broad-spectrum resistance against rice blast. Moreover, genetic analysis revealed that the blast resistance of these three monogenic lines was co-segregated with Pi2/9-RH, suggesting that the Pi2/9 locus or tightly linked loci could be responsible for the resistance. Conclusion The newly developed marker Pi2/9-RH could be used as a potentially diagnostic marker for the quick identification of resistant donors containing functional Pi2/9 alleles or unknown linked R genes. The three new monogenic lines containing the Pi2/9 introgression segment could be used as valuable materials for disease assessment and resistance donors in breeding program